2016
DOI: 10.1016/j.biopsycho.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch response (MMR) in neonates: Beyond refractoriness

Abstract: In the adult auditory system, deviant detection and updating the representation of the environment is reflected by the event-related potential (ERP) component termed the mismatch negativity (MMN). MMN is elicited when a rare-pitch deviant stimulus is presented amongst frequent standard pitch stimuli. The same stimuli also elicit a similar discriminative ERP component in sleeping newborn infants (termed the mismatch response: MMR). Both the MMN and the MMR can be confounded by responses generated by differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…However, we found that a late positive MMR was still elicited in both groups when the stimulus differences were controlled for (i.e., when the duration deviant ERP was compared to the ERP to the same stimulus acting as a standard in the control condition). This supports and extends previous findings that the infant MMR reflects genuine change detection in the auditory system (Kushnerenko et al 2002;Háden et al 2016). Future studies should further investigate, what kind of sensory and cognitive functions these early negative and late positive MMRs reflect at birth.…”
Section: Effects Of the Controlled Duration Paradigmsupporting
confidence: 90%
“…However, we found that a late positive MMR was still elicited in both groups when the stimulus differences were controlled for (i.e., when the duration deviant ERP was compared to the ERP to the same stimulus acting as a standard in the control condition). This supports and extends previous findings that the infant MMR reflects genuine change detection in the auditory system (Kushnerenko et al 2002;Háden et al 2016). Future studies should further investigate, what kind of sensory and cognitive functions these early negative and late positive MMRs reflect at birth.…”
Section: Effects Of the Controlled Duration Paradigmsupporting
confidence: 90%
“…We know that brain responses towards local changes can be observed even in very immature brains such as in preterms ( Mahmoudzadeh et al, 2017 ) and fetuses ( Draganova et al, 2005 , 2007 ). In infants, the so called Mismatch Response (MMR) occurs usually between 200−400 ms after stimulus onset and is comparable to the adult Mismatch Negativity ( Dehaene-Lambertz and Dehaene, 1994 ; Háden et al, 2016 ). In electroencephalographic recordings, this MMR is followed by a Late Slow Wave (LSW) in a time window that can vary between 680 and 1200 ms ( Dehaene-Lambertz and Dehaene, 1994 ; Friederici et al, 2002 ; Basirat et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…As our paradigm and age group are not fully comparable to previous studies, we split our analysis into two parts. First, a literature driven part, where we focused on the time windows reported for the MMR (200−400 ms; Dehaene-Lambertz and Dehaene, 1994 ; Háden et al, 2016 ) and the LSW, using a time window where most previous studies overlapped (800−1000 ms; Dehaene-Lambertz and Dehaene, 1994 ; Friederici et al, 2002 ; Basirat et al, 2014 ). Thereby, we have the hypotheses to find a strong MMR towards local rule violations (first-order regularity), which is modulated by the global rule (second-order regularity).…”
Section: Introductionmentioning
confidence: 99%
“…We know that brain responses towards local changes can be observed even in very immature brains such as in preterms (Mahmoudzadeh et al, 2017) and fetuses (Draganova et al, 2005;Draganova et al, 2007). In infants, the so called Mismatch Response (MMR) occurs usually between 200-400ms after stimulus onset and is comparable to the adult Mismatch Negativity (Dehaene-Lambertz and Dehaene, 1994;Háden et al, 2016). In electroencephalographic recordings, this MMR is followed by a Late Slow Wave (LSW) in a time window that can vary between 680 and 1200ms (Dehaene-Lambertz and Dehaene, 1994;Friederici et al, 2002;Basirat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As our paradigm and age group are not fully comparable to previous studies, we split our analysis into two parts. First, a literature driven part, where we focused on the time windows reported for the MMR (200-400ms;Dehaene-Lambertz and Dehaene, 1994;Háden et al, 2016) and the LSW, using a time window where most previous studies overlapped (800-1000ms; Dehaene-Lambertz and Dehaene, 1994;Friederici et al, 2002;Basirat et al, 2014). Thereby, we have the hypotheses to find a strong MMR towards the local rule violations (first-order regularity), which is modulated by the global rule (second-order regularity).…”
Section: Introductionmentioning
confidence: 99%